Malabar mind - Nair, Anita (Yeti Books, 2002)
heralds the arrival of a major new voice in the mean while-ack-to-real-life-school-of-poetry in Malabar mind, Anita Nair's debut collection of poems, landscapes and minds capes are explored with a rare fluid ease. From the quirky symbol of toddy shops in Malabar - a full bottle of toddy crowned with a red hibiscus to the stressed drone of television newscasters during war time to the apathy of non stick frying pans, Anita Nair rakes through the every day, seizing an unusual moment Love, failure, humor, irony, lust, hope, anguish, beaches, crows, bus journeys, hospitals, just about every aspects of the human existence finds a place in this collection of poems written over a decade